Thiol-based redox control of enzymes involved in the tetrapyrrole biosynthesis pathway in plants - Richter, Andreas S.; Grimm, Bernhard (Frontiers in Plant Science, 2013)
The last decades of research brought substantial insights into tetrapyrrole biosynthetic pathway in photosynthetic organisms. Almost all genes have been identified and roles of seemingly all essential proteins, leading to the synthesis of heme, siroheme, phytochromobilin and chlorophyll, have been characterized. Detailed studies revealed the existence of a complex network of transcriptional and posttranslational control mechanisms for maintaining a well-adjusted tetrapyrrole biosynthesis during plant development and adequate responses to environmental changes. Among others one of the known posttranslational modifications is regulation of enzyme activities by redox-modulators. Thioredoxins and NADPH-dependent thioredoxin reductase C (NTRC) adjust the activity of tetrapyrrole synthesis to the redox-status of plastids. Excessive excitation energy of chlorophylls in both photosystems and accumulation of light-absorbing unbound tetrapyrrole intermediates generate reactive oxygen species, which interfere with the plastid redox poise. Recent reports highlight ferredoxin-thioredoxin and NTRC-dependent control of key steps in tetrapyrrole biosynthesis in plants. In this review we introduce the regulatory impact of these reductants on the stability and activity of enzymes involved in 5-aminolevulinic acid synthesis as well as in the Mg branch of the tetrapyrrole biosynthetic pathway and we propose molecular mechanisms behind this redox control.